A pilot study of the effects of the somatostatin analog pasireotide in postoperative dumping syndrome. Issue 6 (20th April 2014) - Deloose, E.; Bisschops, R.; Holvoet, L.; Arts, J.; De Wulf, D.; Caenepeel, P.; Lannoo, M.; Vanuytsel, T.; Andrews, C.; Tack, J.
Abstract Background Dumping syndrome is characterized by distinct pathophysiological features such as postprandial increase in hematocrit (HT) and pulse rate (PR) and delayed hypoglycemia (HG). Treatment is based on dietary measures and somatostatin analogs (SA), but current SAs have incomplete efficacy, possibly through limited affinity for various somatostatin receptor subtypes. We evaluated the effect of pasireotide, a novel SA with high affinity for 4/5 human somatostatin receptors, on pathophysiological events and symptoms in dumping. Methods Randomized double‐blind placebo‐controlled cross‐over study of nine patients (six women, 47 ± 4 years) with postoperative dumping. Baseline measurements included oral glucose tolerance testing (OGTT), abdominal ultrasound, and dumping symptom severity score (DSSS). Patients were treated for 2 weeks with placebo or pasireotide 300 μg s.c. t.i.d. with a 1‐week wash‐out in a randomized fashion. On day 13 and 14 of each treatment OGTT, DSSS, and solid and liquid gastric emptying (GE) were obtained. Key Results Baseline OGTT was pathological in all patients based on PR (n = 5), HT (n = 1) or HG (n = 7). Compared to placebo, pasireotide suppressed the increase in PR (17.1 ± 2.8 vs 8.2 ± 3.5 bpm; p < 0.05) and late HG (nadir glycemia 55.6 ± 4.3 vs 83.3 ± 9.5 mg/dL; p = 0.007), increased peak glycemia (294.1 ± 33.3 vs 221.0 ± 23.1 mg/dL; p = 0.001) and delayed GE of solids (t1/2 83 ± 23 vs 43 ± 9 min; p = 0.05) and liquids (t1/2 70 ± 10 vs 40 ± 4 min, p = 0.05). The differences in DSSS did not reach statistical significance. Two patients dropped out because of adverse gastrointestinal events under pasireotide. Conclusions & Inferences Pasireotide affects pathophysiological features of both early and late dumping syndrome.